Primary Burkitt lymphoma of the cecal appendix: Case report - Cardeña-Mamani, Rakel (2023)
Introduction: Primary lymphoma of the appendix occurs in 0.015% of all malignant neoplasms of the appendix. The most frequent clinical manifestation is acute appendicitis, and pathological analysis is very important. Case report: Primary lymphoma of the cecal appendix, a 38-year-old man was admitted with acute appendicitis. Macroscopic histopathological study shows diffusely thickened white appendage wall. Microscopically: high-grade Burkitt lymphoma, ACL, CD20, CD10 positive, KI 67 positive 95%, CD3, BCL2, EBV negative. Postoperative: thoracic abdominal tomography showed a tumor in the right iliac fossa without lesions or adenopathies in the abdomen and thorax. The patient was treated with two courses of chemotherapy and a control abdominal CT was performed at 6 months, which showed the initial tumor. At 6 months the patient is stable and controlled. Conclusion: The value of the histopathological study in cecal appendages is emphasized in the presence of primary cecal lymphomas. This case emphasizes the value of the histopathological study in the cecal appendages in the presence of primary cecal lymphomas. Key Words: Primary lymphoma, appendix, Burkitt lymphoma [DeCS/MESH].